NAVIGATING THE ECOSYSTEM OF BIG DATA AND ALGORITHMS AFTER INCARCERATION - Pinch, Annika C (AoIR Selected Papers of Internet Research, 2023)
Formerly incarcerated people, who I will hereafter refer to as “returning citizens”, struggle when reentering society as their criminal record follows them around. In the age of big data and algorithms, finding information about someone’s criminal past is often as simple as typing their name into a google search. Yet there has been little focus on understanding the consequences of big data and algorithmic decisions for everyday people, and how they live with and make sense of these systems. Drawing upon in-depth interviews, I ask: In what ways does the visibility of information about returning citizens’ criminal record as it appears on search engines impact their lives? What strategies (if any) do they use to manage their criminal record in search? Findings explore the difficulties that returning citizens' face in reentering a technologically-driven world that they do not necessarily know how to navigate, which has various consequences in their lives. Yet at the same time, returning citizens find ways of adapting and resisting these systems, with varying degrees of success. Ultimately, these findings add to critiques about the prison-industrial complex and how our reliance on big data and algorithmic systems can perpetuate unequal and colonial power dynamics.